Involvement of impaired CD8+ mucosal-associated invariant T cells and myeloid-derived suppressor cells in polycystic ovary syndrome - Mengting Zhu; Yuping Xu; Caihua Li; Zhimin Lu; Kaihuan Bi; Kangxia Wang; Peipei Guo; Huanhuan Jiang; Yunxia Cao (BMC, 2021)
Abstract Background Immune dysfunction is one of the mechanisms to promote polycystic ovary syndrome (PCOS). Various immune cells have been reported to be involved in the development of PCOS. Meanwhile, the disturbance of metabolism is closely related to PCOS. The aim of this study is to explore the association of mucosal-associated invariant T (MAIT) cells and myeloid-derived suppressor cells (MDSCs) with the metabolic dysfunction in PCOS. Methods 68 PCOS patients and 40 controls were recruited in this study and we collected the peripheral blood of participants' during their follicular phase. The frequencies of MAIT cells and MDSCs were determined by flow cytometry after being stained with different monoclonal antibodies. And the concentrations of cytokines were determined by ELISA. Results Compared to controls with normal metabolism, the frequency of MDSCs, CD8+MAIT cells and CD38+CD8+MAIT cells were significantly decreased in PCOS patients with normal metabolism, however, proportion of CD4+MAIT cells exhibited a noticeable increase. Similar results of CD8+MAIT, CD38+CD8+MAIT cells and reduced expression of IL-17 were observed in PCOS patients with metabolic dysfunction as compared to controls with metabolic disorders. PCOS patients with excessive testosterone levels displayed significantly decreased levels of CD8+MAIT, CD38+CD8+MAIT cells, MDSCs and Mo-MDSCs as compared to PCOS patients with normal testosterone concentrations. PCOS patients with abnormal weight showed a lower level and activation of CD8+MAIT cells. On the contrary, they displayed an enrichment of CD4+MAIT cells. PCOS patients with glucose metabolic disorder displayed a remarkable dysregulation of MDSCs and Mo-MDSCs. MDSCs were positively correlated with MAIT cells. Negative correlations between the frequency of CD8+MAIT cells, CD38+CD8+MAIT cells and body mass index were revealed. CD4+MAIT cells positively correlated with BMI. Mo-MDSCs were found to be negatively related to the levels of 2hour plasma glucose and HOMA-IR index. Conclusion The impairment of CD8+MAIT cells and MDSCs is involved in the metabolic dysfunction of PCOS.